Perceptions of Pregnant Women About the Application of Complementary Therapies to Overcome Emesis Gravidarum - Ketut Novia Arini; Ni Made Rai Widiastuti (Babali Health, 2022)
Introduction: One of the complaints that often arise in early pregnancy (generally in the first months of pregnancy until the end of the first trimester) is nausea and vomiting (emesis gravidarum). Some research results state that the use of aromatherapy can help to reduce complaints of nausea and vomiting during pregnancy. This study aims to determine the perception of pregnant women in applying complementary therapy to overcome emesis gravidarum in the first trimester of pregnancy. Methods: The design used in this study was quantitative descriptive research design with cross sectional approach. This research was conducted in three private midwifery services in South Denpasar Distric. The sample in this study amounted to 100 respondents with purposive sampling technique. This research was conducted for one month, in June 2021. The instrument used is a questionnaire and data were analysed by descriptive analysis. Results: Almost all pregnant women (90%) did not have access to the use of complementary therapies, most pregnant women (78%) did not have traditional and cultural beliefs to use complementary therapies, most pregnant women (58%) had lack of knowledge about complementary therapy, and almost all pregnant women (91%) had a negative perception about the use of complementary therapies to deal with complaints of nausea and vomiting during pregnancy. Conclusion: The conclusion of this study is almost all pregnant women have a negative perception of the use of complementary therapies to treat emesis gravidarum. Expected that more health workers will provide education about complementary therapies to overcome emesis gravidarum.